Konstitusionalitas Standar Pelayanan Minimal - Habib Muchsin Syafingi (Universitas Ahmad Dahlan, 2017)
The purpose of local government is to realize the people’s prosperity through improving services, empowerment, community participation, and enhancement of regional competitiveness. As part of the central government, the local government is responsible for improving public services based on the Minimum Service Standard on the local government obligatory matters that related to the basic needs of the community. The principle of Minimum Service Standard is different from the principle in the Act No. 25 of 2009 about Public Service which tends to emphasize on standard aspects of public goods and public services and more likely focuses toward the realization of good governance. The concern of Minimum Service Standards is the realization of the society’s welfare as one of the state goals. The philosophy of this Minimum Service Standard is the improvement of public’s quality and access to public services which is should be realized in various indicators. The preparation of indicators along with its achievements and its per year target are intended to evaluate easily and also simplify the planning and budgeting process every year. The obligatory matters of local government related to basic needs should be developed by the ministry concerned and implemented by the local government including education, health, public works and spatial, housing and settlement and social. These government duties based on the result of the study that the Minimum Service Standar on those affairs is the further implementation of the constitutional provisions of the 1945 Constitution, so that the drafting and application of Minimum Service Standar has a clear constitutional foundation.